The Dynamics of the Cooperation Between Sea Shepherd Conservation Society and Mexico (Operation Milagro) - Prakoso, Septyanto Galan; Sulistiobudi, Arif; Mulyo, Muhammad Arif; Putra, Ferdian Ahya Al (UIN Sunan Gunung Djati, 2024)
The rapid stream of globalization is giving a wider range of international public relations spheres. As the effects of globalization are the birth of local and international NGOs its activism is shaped from various perspectives. One of the INGOs is Sea Shepherd run based on the idea of environmentalism, especially focused on marine life protection but often accused of being violent and its movement labeled as eco-terrorism. We are using the case of Operation Milagro (2015-2018) between Sea Shepherd and the Mexican government that cooperated. This journal aims to analyze the relationship between two actors including the mechanism of cooperation in Operation Milagro to prevent the extinction of Vaquita Porpoise and the other endangered species in the Cortez Sea, Gulf of California. This article uses relative deprivation theory and transnationalism concepts to gain a new understanding of the analyzed data. We argue that the cooperation of both actors in Operation Milagro is creating a new stage of understanding between both sides through its deprivation of the Sea Shepherd and the cooperation between Mexico and Sea Shepherd. From the point of view of Sea Shepherd, it became a useful tool to reconstruct a new identity as not only an altruistic NGO but also a cooperative nonstate actor. On the other hand, Mexico provided the navy and federal police to facilitate the Sea Shepherd to reach its goal. The author uses some methods such as literature study by collecting data and facts from books, online sites, online journals, and online news. This article also provides some critiques of a problem that came from the effect of cooperation between two actors.